Possibilities of Electronics Engineering Studies in University and College - Bagdanavicius, N.; Andriukaitis, D.; Valinevicius, A. (Elektronika ir Elektrotechnika, 2011)
A natural question often comes to a mind of young people: what to do when studies in the general education schools are over? Forthis reason in this paper a possible variants of choices are discussed, from which it is obvious that it’s the best to continue studies at onceand to acquire a good speciality and only then to look for a job. When selecting a speciality it is recommended to become an electronicsspecialist, because electronics is one of the most advanced areas in our life. Today we find various electronics products in almost everyour step, different and increasingly complex and more "intelligent" electronics systems are being created which facilitate our life.Therefore today there is a great need for specialists who would understand electronics very well and who would be able to design, installand maintain such systems. In the future there will be a need for even more of such specialists. Since in Lithuania at the present time it ispossible to acquire electronics speciality of higher education not only in the university but also in the college a question often emerges:so what is better to choose - university or college? Therefore in this paper study programs of the same type - Electronics - from twohigher education institutions of different level and form the same city of mid-Lithuania are compared. Ill. 1, bibl. 6, tabl. 1 (in English;abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.608